Food Labelling : Nordic Consumers' Attitudes to Food Labelling (Copenhagen : Nordic Council of Ministers, 2007)
This report summarizes the final results of a quantitative study on Nordic consumers' attitudes to food labelling. The study was conducted in the five Nordic countries Sweden, Norway, Denmark, Finland and Iceland. More than 1,000 interviews were conducted in each country. The results of this survey show that information about ingredients, nutritional contents, "best-before-date", and country of origin must be printed clearly on the food package. This is the "top-of-mind" information Nordic consumers want to see on food labels to be able to make a conscious choice when buying food. Furthermore, a majority of Nordic consumers welcome measures to facilitate for consumers to be able to take in information and increase the legibility of food packages. There is strong support for the introduction of a minimum print size and for obligatory labelling information always being laid out in the same format on the package. The purpose of the study was to collect updated information and knowledge on the needs and attitudes of Nordic consumers regarding food labelling. The study aims to contribute with information, knowledge and facts in preparation for the upcoming European Union revision of the food labelling rules.